The Effect of Irreducible Dislocation on Functional Outcomes in Knees With Multiligament Injuries: A Matched-Cohort Analysis. Issue 8 (3rd August 2020) - Zhang, Zhong; Zhang, Kai-Bo; Mao, Bei-Ni; Lai, Si-Ke; Li, Jian; Fu, Wei-Li
Background: Most cases of bicruciate knee dislocation (KD) with associated posteromedial disruption (KD-IIIM) are reducible, but some cannot be reduced by closed reduction because of soft tissue incarceration. Purpose: To compare the clinical characteristics and functional outcomes of KD-IIIM injuries in patients with or without incarceration of soft tissue requiring open or arthroscopic reduction. Study Design: Cohort study; Level of evidence, 3. Methods: This retrospective cohort study of patients with KD was conducted between January 2013 and December 2017 at a single large institution. We applied a 1:2 matching ratio between patients with irreducible KD-IIIM injuries (irreducible group; n = 14) and those with reducible KD-IIIM injuries (control group; n = 28). There were 13 patients in the irreducible group and 25 in the control group who completed follow-up (≥2 years) and were included in our analysis. The efficacy of treatment in patients with KD was evaluated based on range of motion, the Tegner score, the Lysholm score, and the International Knee Documentation Committee (IKDC) score. Results: At the end of follow-up, the mean Tegner score was 4.5 (range, 4-6), the mean Lysholm score was 79.2 (range, 60-95), and the mean IKDC score was 78.6 (range, 60.9-95.4) in the irreducible group. The respective results in the control group were 4.6 (range, 3-8), 83.1 (range, 39-100), and 80.6 (range, 42.5-96.6). These scores did not differ significantly between the 2 groups. Similarly, mean range of motion was similar between groups (irreducible, 118.1°; control, 124.8°). In the irreducible group, the acute subgroup showed significantly higher Lysholm and IKDC scores than the chronic subgroup, while the acute and chronic subgroups in the control group showed no significant differences in these respective outcome scores. Conclusion: In the present study, the treatment of irreducible KD led to similar functional outcomes compared with reducible KD. However, the treatment of chronic irreducible KD led to worse outcomes compared with acute irreducible KD, and therefore, urgent reduction is recommended in these patients.